2011
DOI: 10.1111/j.1440-1746.2011.06925.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of ascites in cirrhosis

Abstract: Ascites is a common complication of liver cirrhosis associated with a poor prognosis. The treatment of ascites requires dietary sodium restriction and the judicious use of distal and loop diuretics, sequential at an earlier stage of ascites, and a combination at a later stage of ascites. The diagnosis of refractory ascites requires the demonstration of diuretic nonresponsiveness, despite dietary sodium restriction, or the presence of diuretic-related complications. Patients with refractory ascites require seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 71 publications
(80 reference statements)
0
37
0
2
Order By: Relevance
“…[1][2][3][4] Sodium dietary restriction and diuretic therapy are the primary treatment modalities for patients with hepatic oedema-manifested ascites. 5 Such diuretics often cause electrolyte imbalance before producing a sufficient amount of diuresis, however, [6][7][8][9] which makes it difficult to make escalating dose adjustments for optimal diuretic effect in patients with hepatic dysfunction. 2,10 Tolvaptan (Samsca TM ; Otsuka Pharmaceutical Co. Ltd, Tokyo, Japan), a novel oral aquaretic agent, is an arginine vasopressin nonpeptide V 2 receptor antagonist, developed for the treatment of clinically significant hypervolaemic or euvolaemic hyponatraemia or less marked hyponatraemia in patients with heart failure, cirrhosis or syndrome of inappropriate antidiuretic hormone.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Sodium dietary restriction and diuretic therapy are the primary treatment modalities for patients with hepatic oedema-manifested ascites. 5 Such diuretics often cause electrolyte imbalance before producing a sufficient amount of diuresis, however, [6][7][8][9] which makes it difficult to make escalating dose adjustments for optimal diuretic effect in patients with hepatic dysfunction. 2,10 Tolvaptan (Samsca TM ; Otsuka Pharmaceutical Co. Ltd, Tokyo, Japan), a novel oral aquaretic agent, is an arginine vasopressin nonpeptide V 2 receptor antagonist, developed for the treatment of clinically significant hypervolaemic or euvolaemic hyponatraemia or less marked hyponatraemia in patients with heart failure, cirrhosis or syndrome of inappropriate antidiuretic hormone.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, hepatic edema has been treated with aldosterone drugs and loop diuretics; however, these sometimes fail to yield sufficient effects despite increase in dose or combined administration. (3) In addition, higher doses and combined administration may upset the balance of electrolytes in the blood and impair renal function. (12) For example, patients with cirrhotic ascites treated with furosemide have been reported to demonstrate significantly increased serum creatinine levels and BUN concentration, as well as significantly decreased glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 99%
“…(2) However, there are cases of refractory ascites in which these drugs have often failed to yield appreciable therapeutic effects, even when used in combination. (3) Tolvaptan, a vasopressin V2 receptor antagonist, can be used to treat hyponatremia, hyponatremia secondary to syndrome of inappropriate antidiuretic hormone secretion, and fluid retention resulting from heart failure. (4) Previously, we reported that tolvaptan improves hepatic edema and ascites, (5) and is approved in Japan for the treatment of refractory ascites in cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…A peritoneovesical shunt known as ALFA pump system is a new investigational technique that has been approved in Europe for the management of ascites but has not yet been approved in the United States [77]. It is implanted subcutaneously and pumps excess peritoneal fluid into the bladder where the patient can eliminate it through normal urination.…”
Section: Managementmentioning
confidence: 99%